(untitled) (Gestión y Gerencia, 2023)
This article shows a technology management (GT) model called FIFE, made up of a set of 30 terms binding to the GT, interrelated with each other in the area of chemical fertilizer production, it was developed through the interpretive structural modeling methodology. The FIFE model contributes mainly to decision-making, policies, systems, procedures, people, alliances, clients, among others. It is made up of 2 large macro levels, the first called "Internal Factors" referring to what the company "does" and "how it does it", the second group called "Environmental Factors" that account for the benefits obtained by the organization. through interest groups; here it intertwines, links and meets short- and long-term needs. In addition, two flows are integrated, one designated "Dynamic Flow" in its trajectory is normally developed in any company in a daily and traditional way, as occurs from the preparation of a good to its reception by a client or consumer and another flow with reverse direction named "Communication Flow", has been that accumulated information data, feedback from the objective and / or subjective appreciation of customers, The FIFE technology management model developed, introduces a new strategic dimension in supply chains in chemical companies, in various aspects: as part of the improvement process, it predicts the research and development activities that are lacking in companies in the fertilizer production sector.